Sistem Pendukung Keputusan Diagnosis Penyakit Stroke menggunakan Metode Fuzzy K-Nearest Neighbor (FK-NN) (Studi Kasus Puskesmas Kendal Kerep Kota Malang) - Yearra Taufan Ardy Rinaldy; Arief Andy Soebroto; Catur Ari Setianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Stroke constitute disease that can cause death and disablement, but the number of patient is still very high. So that new stroke cases do not continue to grow, needed a way for early detection of stroke risk so that people who have the potential to suffer a stroke can take preventative. However, stroke is a complex disease that shows different symptoms between one patient and another. Moreover, the cause of stroke between one person and another person can also be different so that early detection of possible risk of stroke in a patient should be made with care.Decision support systems built using FK-NN are considered capable of assisting early detection of stroke risk quickly, thoroughly, and objectively.support system built with FK-NN will observe to stroke risk factors and calculate using framingham risk score, the method commonly used by doctors to calculate the risk of cardio vascular disease.The system then classifies data using the FK-NN method in the class of low risk stroke, moderate risk stroke, and high risk stroke. The results of this study indicate that the FK-NN is able to properly assist early detection of stroke risk, which resulting in an accuracy of 61.1% when K is 4 and the percentage of training data is 50% of the entire data set.